Caracterización de lixiviados generados en el botadero municipal del cantón La Maná, provincia de Cotopaxi, año 2014 - Coronado Zurita, Javier Darío (2015)
The present research aims to characterize the flow of leachate from the municipal dump La Mana County, Cotopaxi Country, the specific objectives were: to characterize the types of municipal solid waste disposed in the landfill; determine leachate generation, and; their physical and chemical characteristics. Of this research hypothesis was: H1 leachate from the municipal dum La Mana County, do not meet the quality requirements regarding the parameters evaluated in accordance with the standards set out in Table 12 of Annex VI TULSMA 1 book. The MSW characterization, allowed us to determine the per capita production in both the downtown área and the outskirts of the city, 0.72 and 0.62 kg / person / day, respectively; the annual amount of leachate from MSW is 561.5 m3 / year; the contribution of rainwater that precipitates in the landfill is 48967.2 m3 / year; Tontomal Estero is a temporary watercourse thus is variable flow and directly affected by the leak of leachate pond garbage dump; Campaign monitoring of physicochemical put into effect during this investigation parameters it can be concluded that the values of dissolved oxygen (DO), measured in the pool of leachate are well below the standard (0.6 and 1.1 mg / l) , electrical conductivity (EC) between 23900 and 32968 µS / cm, while total dissolved solids (TDS), 23300 and 31700 mg / l are very high; high potential values Hydrogen especially in the pool of leached between 7.7 and 8.2, is due to the coexistence of phases acid gene and gene methane, because the landfill is active and in a phase of transition from youth to middle landfill; Multivariate analysis of the basic physical-chemical parameters of the leachate pond, shows that the most discriminating parameters are: electrical conductivity (EC), total dissolved solids (TDS) The parameters analyzed in the accredited laboratory and compared with the TULSMA Table 12, The technical closure of the landfill is operating since 2009, as well as actions to recover the area of influence of the landfill, through the respective analysis of alternatives are recommended.